Plant editosome database: a curated database of RNA editosome in plants. Issue Volume 47:Issue D1(2019) (26th October 2018) - Li, Man; Xia, Lin; Zhang, Yuansheng; Niu, Guangyi; Li, Mengwei; Wang, Pei; Zhang, Yang; Sang, Jian; Zou, Dong; Hu, Songnian; Hao, Lili; Zhang, Zhang
Abstract: RNA editing plays an important role in plant development and growth, enlisting a number of editing factors in the editing process and accordingly revealing the diversity of plant editosomes for RNA editing. However, there is no resource available thus far that integrates editosome data for a variety of plants. Here, we present Plant Editosome Database (PED;http://bigd.big.ac.cn/ped ), a curated database of RNA editosome in plants that is dedicated to the curation, integration and standardization of plant editosome data. Unlike extant relevant databases, PED incorporates high-quality editosome data manually curated from related publications and organelle genome annotations. In the current version, PED integrates a complete collection of 98 RNA editing factors and 20 836 RNA editing events, covering 203 organelle genes and 1621 associated species. In addition, it contains functional effects of editing factors in regulating plant phenotypes and includes detailed experimental evidence. Together, PED serves as an important resource to help researchers investigate the RNA editing process across a wide range of plants and thus would be of broad utility for the global plant research community.